2016
DOI: 10.4238/gmr.15038234
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of polymorphic microsatellite markers in the endangered species Bretschneidera sinensis Hemsl.

Abstract: ABSTRACT. Bretschneidera sinensis is an endangered species that is mainly distributed in South China. As a tertiary relict and the single species in the Bretschneideraceae family, it has a high conservation value. To investigate the influence of human disturbance on its mating system, 63 new microsatellites were developed using restriction-site-associated DNA sequencing and their polymorphisms were tested on 30 samples from one population. Among the 63 microsatellites, the number of alleles per locus ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Using the same RAD-seq method, we obtained 63 polymorphic loci from 170 candidate loci (37.1%) in an endangered species, Bretschneidera sinensis, in a previous study (Li et al, 2016), but we could obtain only 11 polymorphic loci among the 49 loci (29.7%) identified in this study. In addition, the highest number of alleles per locus was three in D. duperreanum and 16 in B. sinensis with 30 samples from one population.…”
Section: Resultsmentioning
confidence: 66%
“…Using the same RAD-seq method, we obtained 63 polymorphic loci from 170 candidate loci (37.1%) in an endangered species, Bretschneidera sinensis, in a previous study (Li et al, 2016), but we could obtain only 11 polymorphic loci among the 49 loci (29.7%) identified in this study. In addition, the highest number of alleles per locus was three in D. duperreanum and 16 in B. sinensis with 30 samples from one population.…”
Section: Resultsmentioning
confidence: 66%
“…Bretschneidera sinensis Hemsl., a deciduous tree species of montotypic genera belongs to the family Akaniaceae, is a relic species of the Tertiary tropical ora mainly occurring in evergreen broad-leaved or mixed evergreen and deciduous forests in mountainous areas at altitudes of 300-1,700 m above sea level in Southern China (Dong et al 2019;Li et al 2016;Wang et al 2018). The species is listed as endangered on the IUCN Red List of Threatened Species (IUCN 2020, http://www.iucnredlist.org).…”
Section: Plant Species and Collectionsmentioning
confidence: 99%
“…According to recent studies, most of the populations are seriously threatened (Hu et al 2014) and the species also suffers from reproductive failure due to low seed productivity and seed germination rates (Qiao et al 2012). Geographical range of the endangered species extents from Southern China to India, Indo China, Vietnam, and Taiwan (Dong et al 2019;Hu et al 2014;Kumar et al 2017;Li et al 2016;Wang et al 2018). Taiwan is a continental island possessed isolated population of B. sinenis at geographical margin of the Eurasia continent.…”
Section: Plant Species and Collectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, several markers have been used to evaluate the genetic diversity of B. sinensis, including amplified fragment length polymorphism (AFLP) (Hu et al, 2017), random amplified polymorphic DNA (RAPD) (Wang et al, 2008), inter-simple sequence repeats (ISSRs) (Liang et al, 2012;Xu et al, 2013;Hu et al, 2014), microsatellite (SSR) (Guan et al, 2012;Li et al, 2016), and several chloroplast sequence markers (Wang et al, 2018). These results showed that the genetic diversity of B. sinensis was low within populations but relatively high at the species level (Hu et al, 2014(Hu et al, , 2017Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%